Veterinary skills - HSRC Service Account (18245284) (2025)
This chapter analyses the key features of demand for and supply of veterinary services in South Africa. It considers the challenges inherent in reforming not only the system of veterinary education but also features of veterinary service delivery in this country. Veterinary skills are sought after globally and international migration is strongly evident. In South Africa, state-supported veterinary activity historically focused on white commercial farming. Since 1994 the new government has expressed commitment to community animal health services, and to servicing the animal health needs of poor communities. However, as the data analysis in the chapter indicated, government veterinary services are suffering shortages of veterinary skills. The segmentation between private and public practice is reproducing low levels of access to veterinary services and to veterinary education, and those distribution patterns continue to prevail. Between 1994 and 2004 more than 90% of Bachelor of Veterinary Science gradates were white. The most salient change was that after 2001, more females than males graduated. The chapter concludes that attention must be paid to the educational background of students presently unqualified to study for the BVSc, to the promotion of veterinary services as a source of career options, and to the veterinary science curriculum, if present skills shortages are to be adequately addresses.